Pengaruh Capital Adequacy Ratio (CAR) dan Beban Operasional Pendapatan Operasional (BOPO) terhadap Return on Equity (ROE) pada Bank Umum Syariah yang Terdaftar di BEI Periode 2023-2025 - Ilin Mardiah; Rohana (ARZUSIN, 2026)
Profitability is an important indicator for assessing the ability of Islamic commercial banks to manage their capital and operational activities. However, research specifically examining the effects of capital adequacy and operational efficiency on the return on equity of Islamic commercial banks listed on the Indonesia Stock Exchange during the 2023–2025 period remains limited. This study aims to analyze the effects of the Capital Adequacy Ratio (CAR) and Operating Expenses to Operating Income (BOPO) on Return on Equity (ROE). This study employed a quantitative approach with an explanatory design. The sample consisted of four Islamic commercial banks selected from a population of 13 banks through purposive sampling, yielding 12 observations. Secondary data in the form of annual financial statements were collected through documentation and analyzed using descriptive statistics, panel data regression model selection, assumption testing, and hypothesis testing. The results showed that CAR had a positive and significant effect on ROE, whereas BOPO had a negative and significant effect on ROE. Simultaneously, CAR and BOPO had a significant effect on ROE. These findings confirm that improving the profitability of Islamic commercial banks requires productive management of capital adequacy and consistent control of operating costs. Theoretically, this study strengthens the understanding of the relationships among capital structure, operational efficiency, and Islamic bank profitability, while practically, it provides a basis for bank management to optimize capital utilization and improve operational efficiency.